Women's hospital birth experiences in Harar, eastern Ethiopia: a qualitative study using Roy's Adaptation Model. Issue 7 (8th July 2022) - Tefera, Maleda; Assefa, Nega; Roba, Kedir Teji; Gedefa, Letta; Brewis, Alex; Schuster, Roseanne C
Abstract : Objective: The aim of the study was to explore women's birth in public hospitals in the Harari Region of eastern Ethiopia. Design: An exploratory phenomenological qualitative study design was used. Setting: Two public hospitals (Hiwot Fana Specialized University Hospital and Jugal General Hospital). Participants and methods: The study enrolled women who gave birth at the selected hospitals through purposive sampling. We conducted in-depth interviews with 38 women who gave birth to singleton, full-term babies via vaginal delivery (47%; n=18) or caesarean section (53%; n=20) with no pregnancy-related complications. Interviews were audio-recorded and transcribed on the spot and the interviews were analysed using a deductive content analysis approach. Data were analysed using the four components of Roy's Adaptation Model (RAM) as a guiding framework of women's experiences: physiological, self-concept, role and function, and interdependence. Results: Various behaviours were identified: under physiological mode, common behaviours identified included labour pain, fatigue, surgical site pain and anaesthesia-related complication. The women's major problems in self-concept mode were concern for future pregnancy, lack of privacy, newborn health status, relationship with healthcare providers and lack of family support. Due to the prolonged hospital stay and surgical site pain, the women who were unable to care for themselves, their newborn babies and their families adapted poorly to role and function mode. Finally, women who had no family support and who got less attention from healthcare providers reported ineffective adaption for interdependence mode. Conclusions: Application of RAM principles could be used to improve care for Ethiopian women, providing an intervention framework that can gauge and respond to interacting factors that can make women vulnerable to negative birth experiences.